2009
DOI: 10.1038/ijo.2009.35
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic differences in the accuracy of anthropometric indicators of obesity in screening for high risk of coronary heart disease

Abstract: Background Cut points for defining obesity have been derived from mortality data among Whites from Europe and the United States and their accuracy to screen for high risk of coronary heart disease (CHD) in other ethnic groups has been questioned. Objective To compare the accuracy and to define ethnic and gender-specific optimal cut points for body mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WHR) when they are used in screening for high risk of CHD in the Latin-American and the US popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 41 publications
5
52
0
3
Order By: Relevance
“…A recent report of a large cross-sectional study of Latin Americans, nonHispanics whites and blacks, and Hispanics claims WHR to be the most accurate of anthropometric indices in screening for high risk of CHD, with uniform cut points for women but ethnic specific WC and WHR cut points for men. However, there were different techniques employed for waist circumference measurement in the various populations, which could influence the analyses (Herrera et al, 2009). Similarly in the prospective multicentre study of total mortality in Europe, both general adiposity (BMI) and abdominal obesity were associated with the risk of death due to all causes with no clear preference for WHR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of a large cross-sectional study of Latin Americans, nonHispanics whites and blacks, and Hispanics claims WHR to be the most accurate of anthropometric indices in screening for high risk of CHD, with uniform cut points for women but ethnic specific WC and WHR cut points for men. However, there were different techniques employed for waist circumference measurement in the various populations, which could influence the analyses (Herrera et al, 2009). Similarly in the prospective multicentre study of total mortality in Europe, both general adiposity (BMI) and abdominal obesity were associated with the risk of death due to all causes with no clear preference for WHR.…”
Section: Discussionmentioning
confidence: 99%
“…It was also seen that BMI was almost uninformative and WC was less reliable. [15] In a study done by Farrag et al, it was demonstrated that WHR had the best association with coronary artery disease severity. [16] Several factors may account for the discrepancy in findings.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been reported that while HT may prevent the development of atherosclerotic plaques in postmenopausal women 9 , there is no difference in the carotid IMT between women who had and had not used HT 11 . Lipid and lipoprotein metabolism is markedly altered after menopause [12][13][14] with a natural reduction in estrogen levels.…”
Section: Discussionmentioning
confidence: 99%